2021
DOI: 10.6018/analesps.414411
|View full text |Cite
|
Sign up to set email alerts
|

Character strengths as protective factors against engagement in sexting in adolescence

Abstract: El sexting es una nueva forma de interacción sexual en adolescentes que ha sido asociada tanto a problemas psicológicos como comportamientos de riesgo sexual. Aunque varios estudios han examinado la relación entre sexting y rasgos de personalidad, es posible que la asociación con fortalezas del carácter no haya sido explorada. El objetivo de este estudio fue analizar cuales fortalezas de carácter podrían funcionar como factores protectores contra la participación en el sexting, controlando otras variables que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…What remains unknown is their motivations; for instance, it is possible young boys were more likely to reshare as a prank, whereas older youth were more likely to reshare as a form of harassment or bullying. Also, our survey did not include questions regarding other potential risk factors, such as personality traits (Yépez‐Tito et al, 2021) that are associated with a lower likelihood of risky image‐related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…What remains unknown is their motivations; for instance, it is possible young boys were more likely to reshare as a prank, whereas older youth were more likely to reshare as a form of harassment or bullying. Also, our survey did not include questions regarding other potential risk factors, such as personality traits (Yépez‐Tito et al, 2021) that are associated with a lower likelihood of risky image‐related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their research, Peterson and Seligman (2004) identified 24 character strengths, which they classified into six broad virtues (Wisdom and Knowledge, Courage, Humanity, Justice, Temperance, and Transcendence). Overall, character strengths have been considered protective factors against psychological difficulties during adolescence, reducing the risk of psychiatric disorders and violent behaviors or attitudes (Bromley et al, 2006;Ferragut et al, 2013;Kumar & Mohideen, 2021;Ma et al, 2008;Park & Peterson, 2006;Yépez-Tito et al, 2021).…”
Section: Character Strengths and Life Satisfactionmentioning
confidence: 99%
“…Character strengths have likewise been scarcely studied in this context. Research on this topic in Latin America has generally found that strengths may contribute to the development of prosocial behavior (García-Vázquez et al, 2020), improvement in schoolrelated variables (Grinhauz & Castro, 2014), and the prevention of risk behaviors such as sexting (Yépez-Tito et al, 2021).…”
Section: Studies In the Latin American Contextmentioning
confidence: 99%
“…Experiences of relational aggression, bullying, and cyberbullying have also been linked to sending sexts (Doyle et al, 2021 ). Personal qualities such as fairness and authenticity, on the other hand, were protective against sending sexts, suggesting that these character strengths constitute the basis for more measured technology use among young persons and hence should be targeted and enhanced in sexting prevention and intervention programs (Yépez-Tito et al, 2021 ). However, it is noteworthy that the aforementioned research encompasses samples of adolescents across a broad age range from 10 to 19 years.…”
Section: Introductionmentioning
confidence: 99%